1990
DOI: 10.1177/0013164490502021
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Virgilio Teacher Behavior Instrument

Abstract: This study was an attempt to develop an easily coded, research-oriented instrument to assess teacher effectiveness in the class- room. A 35-item Likert format scale was developed which included three subscales of teacher effectiveness: classroom management, instruction, and classroom climate. The results of the study indicated that the Virgilio Teacher Behavior Inventory (VTBI) is a reliable and valid instrument which can be administered with confidence either in elementary or junior high schools. Instrument d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Traditional systems of teacher observation and teacher efficacy include rating scales such as the Structured Teacher Observation Scale (VanTassel‐Baska et al., 2006) and the Virgilio Teacher Behavior Inventory (Teddlie et al, 1990). The Structured Teacher Observation Scale utilizes observer ratings of teacher effectiveness on a three‐point scale that includes perceived teacher lesson planning, elicited student responses, and sustained student focus (VanTassel‐Baska et al., 2006).…”
Section: Current Methods For Conducting Classroom Observationsmentioning
confidence: 99%
“…Traditional systems of teacher observation and teacher efficacy include rating scales such as the Structured Teacher Observation Scale (VanTassel‐Baska et al., 2006) and the Virgilio Teacher Behavior Inventory (Teddlie et al, 1990). The Structured Teacher Observation Scale utilizes observer ratings of teacher effectiveness on a three‐point scale that includes perceived teacher lesson planning, elicited student responses, and sustained student focus (VanTassel‐Baska et al., 2006).…”
Section: Current Methods For Conducting Classroom Observationsmentioning
confidence: 99%
“…Since the 1960s, many observation instruments have been developed to evaluate the quality of teaching (Capie, Johnson, Anderson, Ellet, & Okey, 1980;Evertson, 1987;Evertson & Burry, 1989;Flanders, 1961Flanders, , 1970; Florida Coalition for the Development of a Performance Measurement System, 1983; Houtveen, Booij, De Jong, & Van de Grift, 1999;Houtveen & Overmars, 1996;Inspectie van het Onderwijs, 1998; Office for Standards in Education, 1995;Schaffer & Nesselrodt, 1992;Slavin, 1987;Stallings, 1980;Stallings & Kaskowitz, 1974;Teddlie, Virgilio, & Oescher, 1990;Tricket & Moos, 1974;Veenman, Lem, Voeten, Winkelmolen, & Lassche, 1986;Virgilio, 1987;Virgilio & Teddlie, 1989). Most of these instruments were originally developed for teacher training rather than research purposes.…”
Section: Observation Instrumentsmentioning
confidence: 99%
“…It drew on instruments designed previously in the US and shown to be reliable, including the Special Strategies Observation System (SSOS; see Schaffer et al 1994) and the Virgilio Teacher Observation Instrument (Teddlie et al 1990). Findings from the study in England using the MECORS, including observations of 78 teachers, found that direct instruction was strongly and positively related to effective teaching scales.…”
Section: Empirical Support For the Mecors Instrumentmentioning
confidence: 99%